1987
DOI: 10.1038/325818a0
|View full text |Cite
|
Sign up to set email alerts
|

Homology between Streptomyces genes coding for synthesis of different polyketides used to clone antibiotic biosynthetic genes

Abstract: Many important antibiotics such as tetracyclines, erythromycin, adriamycin, monensin, rifamycin and avermectins are polyketides. In their biosynthesis, multifunctional synthases catalyse iterated condensation of thio-esters derived from acetate, propionate or butyrate to yield aliphatic chains of varying length and carrying different alkyl substituents. Subsequent modifications, including aromatic or macrolide ring closure or specific methylations or glycosylations, generate further chemical diversity. It has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(76 citation statements)
references
References 9 publications
3
73
0
Order By: Relevance
“…(1 987a,b), three of seven streptomycetes not then known to produce polyketidederived metabolites, unexpectedly gave genomic DNA fragments that hybridized with the act probes. One of these, Streptomyesparvzlh was later found to produce the polyketide-derived antibiotic nonactin (cited by Malpartida et al , 1987b), and Streptomyes venepzlehe ISP5230 was subsequently reported to produce jadomycins (Ayer e t al., 1991), a group of pigmented compounds believed from the pattern of isotopic labelling with [13C]acetate to be of polyketide origin (S. Ayer, personal communication). Jadomycin B, the main component of the mixture produced during growth in an isoleucine-containing medium, is glycosylated and has an isoleucine moiety fused into the cyclic structure (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…(1 987a,b), three of seven streptomycetes not then known to produce polyketidederived metabolites, unexpectedly gave genomic DNA fragments that hybridized with the act probes. One of these, Streptomyesparvzlh was later found to produce the polyketide-derived antibiotic nonactin (cited by Malpartida et al , 1987b), and Streptomyes venepzlehe ISP5230 was subsequently reported to produce jadomycins (Ayer e t al., 1991), a group of pigmented compounds believed from the pattern of isotopic labelling with [13C]acetate to be of polyketide origin (S. Ayer, personal communication). Jadomycin B, the main component of the mixture produced during growth in an isoleucine-containing medium, is glycosylated and has an isoleucine moiety fused into the cyclic structure (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular genetic analyses have revealed that the genes for each PKS are clustered in a relatively small region of DNA (22). The gene clusters for numerous polyketide pathways have been detected by hybridization with probes derived from genes coding for proteins that catalyze equivalent reactions in different pathways (25,29).Angucyclinones, a name recently given to naturally occurring benz [a]anthraquinones, are a rapidly growing group of polyketide natural products, involving many bioactive compounds (41). They are now the largest class of known aromatic decaketides.…”
mentioning
confidence: 99%
“…The jad gene cluster was detected by hybridization with the act PKS genes of Streptomyces coelicolor A3(2) (Malpartida et al, 1987 ;Han et al, 1994), and fragments were identified from a restriction map of the region subcloned for sequencing in the phagemid pBluescript II.  analysis (Devereux et al, 1984) of the 2n4 kb EcoRIBamHI segment located two ORFs, assigned to jadI and jadJ.…”
Section: Nucleotide Sequence Of Jadjmentioning
confidence: 99%